PkM Pemanfaatan Kotoran Kuda untuk Pupuk Kompos sebagai Solusi Ramah Lingkungan dalam Pengelolaan Limbah Kandang Kuda: Community Service Program on the Utilization of Horse Stable Manure for Compost as an Eco-Friendly Solution for Horse Stable Waste Management - Santoso, Untung; Saputra, Riza Adrianoor; Diena, Nurin Nisa Farah; Anjardiani, Luki; Rosni, Masyhudah; Budiwati, Nina; Wilda, Kamiliah; Syarbini, Muhammad (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The increasing popularity of equestrian activities today for sports, entertainment, recreation, hobbies, and lifestyles has had a positive impact with the emergence of several horse riding training areas and horse-breeding in South Kalimantan, especially in Banjarbaru City. The horse stables at the horse riding training areas will produce waste in the form of horse manure, both solid (feces) and liquid (urine). Poor waste management of horse manure will hurt the environment. This community service activity aims to provide an eco-friendly solution to the problem of a pile of horse manure in horse stables. Based on the discussions between the community service team and the owner of one of the horse farms in Banjarbaru City, Johnhaus Stable, a solution was provided in the form of training in making compost fertilizer made from horse manure. The training began with a presentation on compost making and was followed by practice in making compost from horse manure. Based on the results of the pre-test and post-test given to participants, there has been a significant increase in the interest and knowledge of the participants regarding compost fertilizer.